Incidence and characteristics of de novo stress urinary incontinence after pelvic organ prolapse vaginal repair (Medical Journal of Indonesia, 2021)
BACKGROUND Some patients who undergo pelvic floor reconstruction for pelvic organ prolapse (POP) may experience a de novo stress urinary incontinence (SUI) postoperatively. We aimed to investigate the incidence and characteristics of de novo SUI in patients who underwent pelvic floor reconstruction at the national referral hospital in Indonesia. METHODS This cross-sectional study evaluated 108 patients who underwent pelvic floor reconstruction due to POP between January 2016 and December 2017. Per the inclusion criteria, 75 women were enrolled using a consecutive sampling. The incidence of de novo SUI was determined 6–12 months postoperatively using the Indonesian version of the questionnaire for urinary incontinence diagnosis and objectively using the cough stress test during gynecologic examination after a negative preoperative prolapse reduction stress test. RESULTS The average age, parity, body mass index, and years since menopause onset were 56.17 (4.67) years, 3.17 (1.07), 28.58 (5.18) kg/m2, and 12.8 (7.0) years, respectively. De novo SUI was seen in 8.0% (6 of 75) patients at 6–7 months postoperatively, with 3 (50.0%) had severe POP and 3 (50.0%) had a mild POP. Most of these patients (4 of 6, 66.7%) had undergone procedures other than colpocleisis for POP reconstruction. CONCLUSIONS The incidence of de novo SUI after gynecologic surgery for POP at a national referral hospital in Indonesia is 8%. Most patients were aged <60 years, had a parity of <4, were nonobese, were menopausal, and had diabetes.